Distribution of body fat and risk of coronary heart disease in men and women. - Canoy, D (2008)
PURPOSE OF REVIEW: Earlier studies investigating the risk of developing coronary heart disease in relation to body fat distribution showed inconsistent results, and any sex-related difference in disease risk has not been adequately examined. This review aims to assess current findings on the prospective association between body fat distribution measures and coronary heart disease in men and women. RECENT FINDINGS: Current epidemiologic evidence suggests that waist circumference and waist-hip ratio, as indicators of abdominal adiposity, are positively related to coronary heart disease in men and women independently of body mass index and conventional coronary heart disease risk factors. But the magnitude and shape of the associations for these abdominal adiposity indices varied with adjustments for mediating and confounding factors. Interestingly, hip waist circumference was inversely associated with coronary heart disease after adjusting for waist circumference. Because waist and hips are positively correlated but have separate and opposite associations with coronary disease, using waist circumference alone may provide underestimated risk estimate if hip girth is not accounted for in the calculation of this risk. SUMMARY: For adipose tissue distribution assessment to be clinically useful, the ideal adiposity phenotype should provide a single risk estimate that captures the separate 'effects' of abdominal and peripheral adiposity. Although far from perfect, waist-hip ratio may capture separate effects of central and peripheral adiposity. This simple and inexpensive measure could be used to help improve coronary heart disease risk assessment.